155k views
4 votes
Justify each step in solving the equation 5(y+3)-11=-y-6 by writing a reason for each statement.

Statements Reasons
5(y+3)-11=-y-6 Given


5(y+3)=-y+5


5y+15=y+5


5y=-y-10


6y=-10


y=-5/3 Division Property of Equality/Reduce


Please help!!!

User Snoone
by
5.2k points

1 Answer

5 votes

Step-by-step explanation:

5(y+3)-11=-y-6 Given

5(y+3)=-y+5 . . . . addition property of equality (11 is added)

5y+15=y+5 . . . . . distributive property (5 is distributed)

5y=-y-10 . . . . . . . addition property of equality (-15 is added)

6y=-10 . . . . . . . . . addition property of equality (y is added)

y=-5/3 Division Property of Equality/Reduce

User Gunaseelan
by
5.5k points